Rare side effect of a common drug - Kadagud, Anuja M.; Hiremath, Shruti Basayya; Warad, Vijaykumar G.; Badiger, Sharan; Kattimani, Ravi (International Journal of Advances in Medicine, 2021)
Metronidazole is most commonly used antimicrobial agent to treat various anaerobic bacterial and parasitic infections. Metronidazole induced side-effects are usually mild but neurotoxicity associated with it is rare. Here we report 33 year old para 1 living 1 (P1L1) post lower segment cesarean section (LSCS) discharged with metronidazole for 14 days presented to us with signs and symptoms of neurotoxicity with magnetic resonance imaging (MRI) brain findings consistent to metronidazole toxicity.